The Catalans in Sardinia and the transformation of Sardinians into a political minority in the twelfth to the fifteenth centuries. Issue 3 (27th May 2019) - Gallinari, Luciano
ABSTRACT: This article outlines relations between the Catalan-Aragonese and the Sardinians, between the twelfth and fifteenth centuries, encompassing the integration of Sardinia first into the Crown of Aragon and then into the Crown of Spain. There was a political minority in the Giudicato of Arborea, a polity that was the last institutional heir to the ancient Arconate/ Giudicato of Sardinia. This group was probably part of the oligarchy of the Giudicato ; from the 1380s to the 1410s, it tried to overthrow the government of the Bas Serra dynasty and return to the allegiance of the kings of Aragon. It has been argued that the population of Arborea supported the policy of war against the Aragonese kings led by the judges of Arborea until the disappearance of the Giudicato . The political and social dynamics within Arborea and between the Giudicato and the Aragonese kings demonstrate the role of the discourse of the political minority.